What is the contemporary state of amber tourism research? Bibliometric analysis of selected databases - Paprzycka, Joanna (Turystyka – to znaczy co? Uroboros czy Feniks, 2025)
This article is devoted to a bibliometric analysis prepared on the basis of a review of the Scopus and Science Direct databases. The topic presented is part of the research conducted for the needs of a doctoral dissertation prepared at the University of Lodz. The aim is to present selected results from the database searches as a basis for the selection of publications serving to specify a research gap and narrow the research issue for the needs of further academic work.